ANALISIS TINGKAT KESEHATAN BANK DENGAN METODE RGEC PERIODE 2017-2022 (Studi Kasus: PT Bank JTrust Indonesia) - Cindy Anisya Zahra (2023)
The purpose of this final project is to assess the health level of PT Bank JTrust Indonesia using the RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital) method with the RBBR (Risk-Based Bank Rating) approach. The results of this study indicate that the overall health level of PT Bank JTrust Indonesia during the period of 2017-2022, the credit risk analysis with the NPL ratio falls under the "Healthy" category, and the liquidity risk analysis with the LDR ratio falls under the "Very Healthy" category. The GCG component is rated as "Good," while the ROA ratio is categorized as "Unhealthy." The analysis of the CAR ratio indicates that it falls under the "Very Healthy" category. Keywords: Bank Health Level, RGEC, Risk Profile, Good Corporate Governance, Earnings, Capital, Banking.